Socially Vulnerable Youth and Volunteering in Sports: Analyzing a Brussels Training Program for Young Soccer Coaches - Buelens, Evi (Social Inclusion, 2015)
A considerable number of young Europeans live or risk ending up in socially vulnerable situations. Different social channels (e.g., education, on the job training, leisure) exist through which youths can enhance their chances to improve their social position. There is a growing belief that sports in particular can help personal and social development of socially vulnerable youths. Nevertheless, there is little understanding of the mechanisms through which sports can foster development. In addition to participating in sports, volunteering in sports is also regarded as providing developmental opportunities for socially vulnerable youths. Today, however, there is an underrepresentation of socially vulnerable youths in volunteering and volunteer training programs. A case study in Brussels was set up within a volunteer soccer training program focused on socially vulnerable youths. A qualitative research design was used to analyze developmental experiences of participants (n = 11) and program organizers (n = 3). The study also aimed to gain more insight into the mechanisms underlying the program. Participating youths indicated development in both technical and key competences. It is concluded that a systematic approach of the volunteer training program can play an important role in the development of competences of socially vulnerable youths both as a volunteer and an individual.